An Updated Description of More Than 5, 000 Procedures from the Danish Hip Arthroscopy Registry. (4th November 2020) - Mygind-Klavsen, Bjarne; Kraemer, Otto; Hölmich, Per; Lund, Bent
Abstract : Background: The Danish Hip Arthroscopy Registry (DHAR) started as a web-based prospective registry in 2012. The aim of this study was to evaluate and report epidemiologic and perioperative data from 5, 333 procedures and to describe the development of the DHAR. Methods: The DHAR collects data from patients prospectively at the time of inclusion (preoperative evaluation) and at 1, 2, 5, and 10 years after arthroscopic hip surgery. The surgeon reports surgical data at the time of surgery. The DHAR uses a number of validated patient-related outcome measures (PROMs): the Copenhagen Hip and Groin Outcome Score (HAGOS), Hip Sports Activity Scale (HSAS), EuroQol 5 Dimensions (EQ-5D), and a numeric rating scale for pain (NRS pain). Results: Of the 5, 333 procedures, 58% were done in female patients. The mean age was 37.7 years. The mean duration of surgery was 78 minutes, and the mean duration of traction was 45 minutes. Combined cam and pincer resections were performed in 64% of the patients, and labral repair was done in 82%. The most common type of acetabular chondral damage found was Beck grade-2 lesions (43%). Grade-3 and 4 changes were seen in 29% and 11% of the patients, respectively. The 1-year HAGOS PROM values increased to a median of 69.1 (interquartile range [IQR], 68.2 to 70.0) for pain, 64.9 (IQR, 64.0 to 65.7) for symptoms, 71.3 (IQR, 70.3 to 72.3) for activities of daily living, 56.2 (IQR, 55.1 to 57.4) for sports, 42.2 (IQR, 40.8 to 43.5) for physical activity, and 50.7 (IQR, 49.7 to 51.8) for quality of life, and the 1-year EQ-5D increased to a median of 0.75 (IQR, 0.74 to 0.76). Five-year outcomes for 383 patients showed a significant increase in all PROMs (p < 0.05). Conclusions: Patients referred for hip arthroscopy reported pain, functional disabilities, and a decreased activity level and quality of life prior to surgery but demonstrated improvements after 1 and 5 years. The problems with developing and maintaining a large clinical registry are described. The development of a national clinical registry for hip arthroscopy was considered successful. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.